Pengembangan Sarana dan Prasarana Kawasan Pantai Labombo Kota Palopo Berbasis Wisata - Ulviah Hikmawaty; Slamet Trisutomo; Mukti Ali (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2018)
Labombo Beach which is located in Palopo City is one area that has the potential to be developed as a nature tourism area based on the Palopo City RTRW. Therefore, in its development required adequate tourist facilities and infrastructure. This study aims to identify the potential and problems, determine the needs of facilities and infrastructure and arrange direction for the development of facilities and infrastructure in the Labombo Coastal Area. Data collection methods used were observation, interviews, questionnaires and literature studies. The analytical method used is the analysis of the Attraction Attraction (ODTW), descriptive qualitative, quantitative, spatial analysis, photo mapping, and SWOT. The results of this study are, the potential and problems in the Labombo Coastal Area based on the characteristics of the area show considerable potential. However, the availability of infrastructure that is minimal and still inadequate is one of the factors inhibiting its development as a tourist area. Therefore, the direction of the development of Labombo Beach, among others, is increasing the availability of supporting tourism infrastructure in the form of a tourist information center, public toilets, bridges, docks, gazebos, applying the concept of zoning and planning other infrastructure, namely road networks and drainage.